2009
DOI: 10.1093/cjres/rsp028
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and regions: building understanding of the metaphor

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
399
0
62

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 629 publications
(462 citation statements)
references
References 19 publications
1
399
0
62
Order By: Relevance
“…Some critics point to the term's continued 'fuzziness' and the need to avoid a too rapid (and simplistic) transfer from ecological systems literature into a public policy domain (Pendall et al, 2010). As one review of the term argues, '.there is a need to proceed with caution and ensure that policy fixes do not exceed the capability of the research base to justify them.…”
Section: A Contested Concept ?mentioning
confidence: 99%
“…Some critics point to the term's continued 'fuzziness' and the need to avoid a too rapid (and simplistic) transfer from ecological systems literature into a public policy domain (Pendall et al, 2010). As one review of the term argues, '.there is a need to proceed with caution and ensure that policy fixes do not exceed the capability of the research base to justify them.…”
Section: A Contested Concept ?mentioning
confidence: 99%
“…Path dependence theories set up in the course of resilience investigations have examined the historical background to the development of crises (Pendall, 2007), the effect of the vision created by certain social systems on the development Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 8:54 AM of a region (Grabher, 1993), and the structural change ensuing in the region (Martin, 2010). The success of the structural change, however, depends on how local companies and institutions are able to form an alliance.…”
Section: On Regional Resilience Competitiveness and Homogeneitymentioning
confidence: 99%
“…In their analyses, they were looking for an answer to how the regions react to the economic challenges of the business environment. Studies and models found in the literature (Martin, 2010;Pendall et al, 2007) usually interpret and examine the whole region as a single entity. The indices used in the models track the temporal changes of the economic indicators concerning the whole region.…”
Section: Introductionmentioning
confidence: 99%
“…Elemzésükben választ kerestek arra, hogy az egyes régiók hogyan reagálnak az üzleti környezet gazdasági kihívásaira. A szakirodalomban (Martin, 2010;Pendall, et al, 2007) fellelhető tanulmányok és modellek általában a régiót egységes egészként értelmezik és vizsgálják. A modellekben használt indikátorok a régiók egészét érintő gazdasági mutatók időbeli változását követik.…”
Section: Bevezetésunclassified
“…A rugalmasság vizsgálata során felállított útfüggőségi elméletek vizsgálták a válságok kialakulásának történeti hátterét (Pendall, 2007), valamint az egyes társadalmi rendszerek által kialakított jövőkép hatását a régió fejlődésére (Grabher, 1993). Martin (2010) útfüggőségi modellje szerint a régióban bekövetkező szerkezetváltás, az erőforrások kombinálása rövidtávon előnyösebb és hatékonyabb választ tud adni a problémára, mint a meglévő szerkezet folyamatos kiigazítása.…”
Section: A Regionális Rugalmasságról Versenyképességről éS Homogenitunclassified